Oral pulmonary vasoactive drugs achieve hemodynamic eligibility for liver transplantation in portopulmonary hypertension. Issue 3 (March 2017) - Legros, Ludivine; Chabanne, Céline; Camus, Christophe; Fournet, Maxime; Houssel-Debry, Pauline; Latournerie, Marianne; Jezequel, Caroline; Rayar, Michel; Boudjema, Karim; Guyader, Dominique; Bardou-Jacquet, Edouard
Abstract: Background and aims: Portopulmonary hypertension (POPH) hampers survival of patients with cirrhosis and portal hypertension and may preclude liver transplantation (LT). Management of such patients with oral pulmonary vasoactive drugs (PVD) has not been standardized. Our aim was to assess the efficacy and safety of oral PVD for management of POPH. Methods: All patients treated by oral PVD (bosentan, ambrisentan, sildenafil, tadalafil) for POPH were retrospectively studied. Significant response was defined for the patients who reached the following LT eligibility criteria: mean pulmonary artery pressure (MPAP) <35 mmHg or MPAP between 35 and 50 mmHg with pulmonary vascular resistance (PVR) <250 dyn s cm −5 . Results: 20 patients were followed for 38 (19–57) months. Oral PVD improved MPAP (−8 [−19, +2] mmHg), PVR (−201 [–344, –68] dyn s cm −5 ) and 6-min walk distance (+52 [−51, +112] m). Fifty-three percent of evaluable patients reached eligibility to LT criteria, of whom 5 were transplanted. Baseline MPAP > 51 mmHg and/or PVR > 536 dyn s cm −5 predicted non response to treatment. Five-years survival was 53%. No worsening of cirrhosis or serious adverse effect was recorded. Conclusion: Oral pulmonary vasoactive drugs are safe in cirrhotic patients with POPH. These treatments improved hemodynamic conditions allowing patients access to liver transplantation eligibility.